2019
DOI: 10.1049/iet-pel.2018.5582
|View full text |Cite
|
Sign up to set email alerts
|

Improved single‐phase self‐synchronised synchronverter with enhanced dynamics and current limitation capability

Abstract: Inertia-less power converters are one of the main obstructions to increase the penetration level of distributed energy resources in the utility grid. The stability of the power system mainly depends on the system inertia. Virtual synchronous machine and synchronverter-based grid-tied inverters have been introduced as a solution to this problem. Here, a modified selfsynchronised synchronverter is introduced to enhance the dynamic response of the active power loop and to limit the injected active/reactive power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…The small signal analysis may not replicate the complete non-linearity of the system, as it linearises the system around an operating point. However, the small signal analysis method is robust enough to study transient responses and design control parameters as shown in [4], [8], [10] and [15]. Hence, small signal analysis is applied for the proposed pre-synchronisation method as well.…”
Section: Transient Response Analysis Of Proposed Pre-synchronisation mentioning
confidence: 99%
“…The small signal analysis may not replicate the complete non-linearity of the system, as it linearises the system around an operating point. However, the small signal analysis method is robust enough to study transient responses and design control parameters as shown in [4], [8], [10] and [15]. Hence, small signal analysis is applied for the proposed pre-synchronisation method as well.…”
Section: Transient Response Analysis Of Proposed Pre-synchronisation mentioning
confidence: 99%
“…Meanwhile, the steady-state power deviation has been nullified through a PI controller (see Fig. 10) [59], [60].…”
Section: ) Modified Single-phase Synchronvertersmentioning
confidence: 99%
“…However, the proposed synchronverter operates as a current source which contradicts the behaviour of original synchronverter. Similarly, the RPL has been retained and the RePL has been modified with a PI controller for voltage regulation [59]. The single-phase power values have been derived through orthogonal signal generation using a SOGI.…”
Section: ) Modified Single-phase Synchronvertersmentioning
confidence: 99%
“…Second category is to modify the operation of the interfacing power electronic converters to emulate as a synchronous generator. This method is popularly known Virtual Inertia, synchro-converter [16]- [26] etc. This paper mainly concentrates few of the methods proposed by the researches to improve the transient stability of the PV -Grid connected system.…”
Section: Introductionmentioning
confidence: 99%